2020
DOI: 10.3389/fonc.2020.01179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hematologic Toxicity and Bone Marrow Compensatory Response in Head and Neck vs. Cervical Cancer Patients Undergoing Chemoradiotherapy

Abstract: Background: Hematologic toxicity is a critical problem limiting treatment delivery in cancer patients undergoing concurrent chemoradiotherapy. However, the extent to which anatomic variations in radiation dose limit chemotherapy delivery is poorly understood. A unique natural experiment arises in patients with head and neck and cervical cancer, who frequently undergo identical chemotherapy but receive radiation to different regions of the body. Comparing these cohorts can help elucidate to what exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Significant hematologic changes in the leukocyte counts after surgery and during RT as well as hemoglobin levels after surgery have been presented in our study. This decrease in leukocyte counts during RT was consistent even when patients with chemotherapy prior to RT were excluded and might most likely be explained by considering the results of prior studies in cervical cancer patients [45,46] with hematologic toxicity and decreases in neutrophil, lymphocyte and platelet counts due to bone irradiation that goes along with pelvic RT and similar target volumes. Our study could not confirm a significant reduction in platelet counts for uterine sarcoma, but of note, cervical cancer radiotherapy is ad-ministered with concurrent weekly cisplatin compared to RT only in uterine sarcoma, which might mostly likely have contributed to increased toxicity.…”
Section: Discussionsupporting
confidence: 65%
“…Significant hematologic changes in the leukocyte counts after surgery and during RT as well as hemoglobin levels after surgery have been presented in our study. This decrease in leukocyte counts during RT was consistent even when patients with chemotherapy prior to RT were excluded and might most likely be explained by considering the results of prior studies in cervical cancer patients [45,46] with hematologic toxicity and decreases in neutrophil, lymphocyte and platelet counts due to bone irradiation that goes along with pelvic RT and similar target volumes. Our study could not confirm a significant reduction in platelet counts for uterine sarcoma, but of note, cervical cancer radiotherapy is ad-ministered with concurrent weekly cisplatin compared to RT only in uterine sarcoma, which might mostly likely have contributed to increased toxicity.…”
Section: Discussionsupporting
confidence: 65%
“…When receiving local radiotherapy alone, metabolic activity increased in the unirradiated bone marrow. The compensatory response is reduced during concurrent chemoradiotherapy owing to the superimposed toxicity, which increases the incidence of HT [12,13]. The hematopoietic stem cells in the red bone marrow can self-renew and regenerate, which is the basis of maintaining normal hematopoietic function and repairing bone marrow injury.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue toxicity is the main obstacle to overcome in planning an effective radiation dose. [20,21] In a recent study, Vitzthum et al [20] compared the hematological toxicity in head/ neck vs cervical cancer patients undergoing CRT. They found that the peripheral cell counts significantly declined over the course of treatment in each group of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Both patient groups exhibited different patterns of subacute compensatory response in the bone marrow, and the higher volume of active marrow irradiated in cervical cancer patients appears to be a significant independent contributor to a faster depletion of circulating neutrophil, lymphocyte, and platelet cell types. [20] To reveal the hematological damage by RT in gastric patients, we investigated and compared the blood parameters before and after the planning treatment. The hematological parameters albumin, WBC, and PLT significantly lowered after RT; however, we could not find a statistical difference for the total and direct bilirubin, hemoglobin, and neutrophil amounts probably due to the different treatment modalities and durations compared with the literature.…”
Section: Discussionmentioning
confidence: 99%